TAMI-08. A TALE OF TWO TELOMERE MAINTENANCE MECHANISMS: TERT EXPRESSION AND THE ALT PATHWAY INDUCE UNIQUE MRS-DETECTABLE METABOLIC REPROGRAMMING IN LOW-GRADE GLIOMAS - Viswanath, Pavithra (Neuro Oncol, 2020)
Telomeres are nucleoprotein structures at chromosomal ends that shorten with cell division and constitute a natural barrier to proliferation. In order to proliferate indefinitely, all tumors require a telomere maintenance mechanism (TMM). Telomerase reverse transcriptase (TERT) expression is the TMM in most tumors, including low-grade oligodendrogliomas (LGOGs). In contrast, low-grade astrocytomas (LGAs) use the alternative lengthening of telomeres (ALT) pathway as their TMM. As molecular hallmarks of tumor proliferation, TMMs are attractive tumor biomarkers and therapeutic targets. Non-invasive imaging of TMM status will, therefore, allow assessment of tumor proliferation and treatment response. However, translational methods of imaging TMM status are lacking. Here, we show that TERT expression and the ALT pathway are associated with unique magnetic resonance spectroscopy (MRS)-detectable metabolic reprogramming in LGOGs and LGAs respectively. In genetically-engineered and patient-derived LGOG models, TERT expression is linked to elevated (1)H-MRS-detectable NAD(P)/H, glutathione, aspartate and AXP. In contrast, the ALT pathway in LGAs is associated with higher α-ketoglutarate, glutamate, alanine and AXP. Importantly, elevated flux of hyperpolarized [1-(13)C]-alanine to pyruvate, which depends on α-ketoglutarate, is a non-invasive in vivo imaging biomarker of the ALT pathway in LGAs while elevated flux of hyperpolarized [1-(13)C]-alanine to lactate, which depends on NADH, is an imaging biomarker of TERT expression in LGOGs. Mechanistically, the ALT pathway in LGAs is linked to higher glutaminase (GLS), a key enzyme for α-ketoglutarate biosynthesis while TERT expression in LGOGs is associated with elevated nicotinamide phosphoribosyltransferase (NAMPT), a key enzyme for NADH biosynthesis. Notably, TERT expression and the ALT pathway are linked to MRS-detectable metabolic reprogramming in LGOG and LGA patient biopsies, emphasizing the clinical validity of our observations. Collectively, we have identified unique metabolic signatures of TMM status that integrate critical oncogenic information with noninvasive imaging modalities that can improve diagnosis and treatment response monitoring for LGOG and LGA patients.